Drivers of agrifood system transformation in Odisha - Mishra, Sarba Narayan; Mishra, Subhrajyoti; Ajmani, Manmeet Singh; Ashok, K.R.; Behura, Debdutt; Das, Manoj Kumar (International Food Policy Research Institute, 2024)
Globally, agrifood systems (AFS) are experiencing rapid transformation driven by a range of factors. This transformation process is also observed across several states of India, including Odisha. This study develops a conceptual framework to examine the key drivers of AFS transformation in Odisha. Analytical tools, including trend analysis, the Simpson Index, and the Just-Pope Yield function, were used to assess the impact of various determinants of changes in the state’s AFS. The report presents an analysis and breakdown of growth trends in the agrifood system over the last two decades, identifies constraints and opportunities for future growth, and evaluates the coherence of government agricultural policies, offering direction for future policies to manage and motivate AFS transformation in Odisha. Odisha’s AFS is characterized by diverse stakeholders, with smallholder farmers facing significant challenges, particularly from climate-induced shocks and the volatility in agricultural gross value added (GVA). Among farming households, wage income now surpasses earnings from traditional agricultural activities, such as crop cultivation and livestock production. Several demographic and economic factors, including population growth, urbanization, and rising incomes, have profoundly influenced the structure and operations of the AFS, as evidenced by increasing demand for higher-value food products, including processed foods. The adoption of innovative technologies, such as Bt cotton and climate-resilient crop varieties, has enhanced farm productivity and profitability, driving crop diversification. Increased use of purchased farm inputs, such as high-yielding variety seeds, inorganic fertilizers, pesticides, and agricultural machinery, has further shaped Odisha’s agrifood landscape. Government policies, including higher annual budget allocations for irrigation infrastructure, climate-resilient technologies, subsidized credit and insurance, and farmer welfare programs, have been instrumental in shaping Odisha’s AFS. However, despite strong growth, the fisheries sector remains underfunded compared to other subsectors. Improved rural infrastructure—such as expanded road and irrigation networks, grain and cold storage facilities, mobile connectivity, and improved market access—has contributed positively to AFS transformation in the state. Additionally, rural organizations, including farmer producer organizations (FPO), self-help groups (SHG), Krishi Vigyan Kendra (KVK) and agricultural extension centers, have played a crucial role in advancing the state agricultural initiatives, such as Shree Anna Abhiyan, the special programme for promotion of millets in tribal areas of Odisha. The increasing number of hotels and restaurants, coupled with rising investments in the agrifood industry, underscores the expanding role of the agro-processing sector in Odisha’s economy. To revitalize rural economies, efforts should focus on boosting rural non-farm sectors, enhancing farm productivity, and strengthening infrastructure, particularly logistics and cold chain facilities. Investments in agrifood processing, promoting digital marketing, and fostering climate-resilient technologies are also important. Small farmers need support through strengthened FPOs, better access to quality seeds and mechanization, especially women farmers. Policies should be modified to promote increased crop and enterprise diversification, fishery sector growth, and organic farming. Agrifood parks and research in processing technologies can increase value addition and promote entrepreneurship within the AFS. Finally, solar energy integration will ensure sustainability and economic growth across agrifood value chains.